Environmental Approaches for the Benchmarking of International Experience in the Use of Scientific Research in State Strategic Planning for a Sustainable Development - TAUBAYEV, Ayapbergen; ARKENOVA, Zhadyra; MUSSATAYEVA, Assemgul (Journal of Environmental Management and Tourism, 2022)
The prospects for sustainable development of the Republic of Kazakhstan and the factors influencing its development are considered as a long-term direction of structural policy, which makes it possible to create and actively develop sustainable development programs, minimize risks, increase competitiveness and open up new opportunities that take into account the negative impact on the environment. In this regard, the paper analyzes the mechanisms of scientific support of state strategic planning in the framework of environmental management, using the scientific potential of the academic environment, taking into account the opinion of the public and the expert community, as well as the creation of specialized research institutes. The results of this study will indicate the ways in which the innovative potential conducted by the public administration could use the potential of science to improve the efficiency of public policies in environment management for a sustainable development.